2022
DOI: 10.3390/ijerph20010503
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Air Metabolome Analysis for Pulmonary Arterial Hypertension Fingerprints Identification—The Preliminary Study

Abstract: Pulmonary arterial hypertension (PAH) is a rare disease with a serious prognosis. The aim of this study was to identify biomarkers for PAH in the breath phase and to prepare an automatic classification method to determine the changing metabolome trends and molecular mapping. A group of 37 patients (F/M: 8/29 women, mean age 60.4 ± 10.9 years, BMI 27.6 ± 6.0 kg/m2) with diagnosed PAH were enrolled in the study. The breath phase of all the patients was collected on a highly porous septic material using a special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The evaluation of metabolic features and biochemical pathways associated with PAH can provide a holistic insight into the molecular mechanisms, improve the current diagnostic or treatment schedules, identify subphenotypes of the disease and propose new therapeutic targets. The results of recently published studies have confirmed that metabolic dysregulation is a common feature of various clinical types of PAH 8 , 11 , 12 , 17 20 . Herein, a global plasma untargeted metabolomics with the use of the LC–MS technique was applied to characterize the metabolic phenotype of PAH patients.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The evaluation of metabolic features and biochemical pathways associated with PAH can provide a holistic insight into the molecular mechanisms, improve the current diagnostic or treatment schedules, identify subphenotypes of the disease and propose new therapeutic targets. The results of recently published studies have confirmed that metabolic dysregulation is a common feature of various clinical types of PAH 8 , 11 , 12 , 17 20 . Herein, a global plasma untargeted metabolomics with the use of the LC–MS technique was applied to characterize the metabolic phenotype of PAH patients.…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, most of the recent metabolomics-based studies of PH in the human population have considered different etiologies of the disease 11 , 12 or were focused on the analysis of lung tissue samples 13 , 14 . Evaluation of the tissue metabolic signature provides a specific insight into the molecular mechanisms of PAH, however, it is invasive and limited by the number and amount of samples available for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were obtained from the metabolomics analysis of exhaled breath. The latter was tested with gas chromatography associated with mass spectrometry [43].…”
Section: Pah Pathogenesismentioning
confidence: 99%